2023
DOI: 10.2147/rmhp.s393311
|View full text |Cite
|
Sign up to set email alerts
|

Physical Inactivity is Associated with Job Burnout in Health Professionals During the COVID-19 Pandemic

Abstract: Background:The pandemic has drastically impacted lifestyles, including the frequency, duration, and intensity of physical activity, which, in turn, leads to negative effects on job burnout among healthcare workers. Objective: This study evaluated the association between the level of physical activity and job burnout in a sample of health professionals during health emergency. Methods: In this cross-sectional study, 300 workers working in a public hospital, located in the city of Rioja, Department of San Martin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 28 publications
(9 citation statements)
references
References 38 publications
0
9
0
Order By: Relevance
“…For example, a recent systematic review found a burnout rate between 4.3 and 90.4% among health care workers who were on the frontline during the COVID-19 pandemic ( 2 ). Similarly, the results of another study conducted during the pandemic reported that 62 and 21% of the professionals had medium and high burnout, respectively ( 4 ). The current study was conducted during the pandemic.…”
Section: Introductionmentioning
confidence: 78%
See 2 more Smart Citations
“…For example, a recent systematic review found a burnout rate between 4.3 and 90.4% among health care workers who were on the frontline during the COVID-19 pandemic ( 2 ). Similarly, the results of another study conducted during the pandemic reported that 62 and 21% of the professionals had medium and high burnout, respectively ( 4 ). The current study was conducted during the pandemic.…”
Section: Introductionmentioning
confidence: 78%
“…Similarly, a wide variability was found in the burnout rate among health care workers during the COVID-19 pandemic, ranging from 4.3 to 90.4% ( 2 ). In addition, other studies reported that 62 and 21% of health professionals presented medium and high levels of burnout, respectively ( 4 ). Additionally, burnout rates in palliative care health professionals were reported to range from 3 to 66% ( 3 ).…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“… 62 It is possible that working directly with COVID-19 affected patients generates a type of cumulative vicarious trauma for frontline workers, which could have direct effects on their level of mental health. 63 …”
Section: Discussionmentioning
confidence: 99%
“…Tacchini et al (18) provided two categorization approaches, one based on logistic regression and the other on a community-developed new version of the Boolean algorithm. Even though the training set comprised fewer than 1 % of the posts, higher than 99 % classification accuracy was still attained on a dataset of 15 500 Facebook posts and 909 236 individuals.…”
Section: Literature Reviewmentioning
confidence: 99%